Macular Retinoschisis and Its Semiotic Importance: A Case Report - Golubovikj, Milena; Tateshi, Bekim; Isjanovski, Igor; Buzarovska, Karolina (Walter de Gruyter GmbH, 2015)
Abstract Introduction. The concept of retinoschisis means splitting of the layers of neural retina. It can happen equally at the peripheral part of retina, as well as in the region of macula when we talk about macular retinoschisis. Macular retinoschisis appears as one of the characteristics of a few hereditary diseases. According to the ophthalmoscopes’ picture it can easily be mixed with cystoid macular edema. Even though macular changes, in both cases, during time lead to decrease of visual acuity, distinction of macular changes is of semiotic significance in differential diagnosis of retinal diseases, which is important from a broader medical aspect. The aim of this paper is, by presenting a case with a rare hereditary disorder, to show the importance and complementarities of diagnostic methods, especially OCT and its meaning in establishing the correct diagnosis. Case report. The paper presents a patient with macular retinoschisis, as a part of Goldmann-Favre vitreoretinal degeneration. It is a hereditary disorder, which in addition to schisms changes in the macula is characterized by changes in the pigmented epithelium at the medial part of retina. OCT finding in our patient showed cystic hyporeflexive change in the fovea, with palisade oriented smaller hyporeflexive changes, between plexiform layers and in the inner granular layer of the macula. On fluorescein angiography the leakage of the fluorescein in the macular region was absent, but the changes on the level of pigmented epithelium in the area of medial retina were evident. However, perimetry did not show defect in the visual field. Conclusion. Newer diagnostic methods, such as optical coherence tomography, proved their importance in the decision making process and in making the right diagnosis in macular lesions. Beside the fact that the correct diagnosis of the disorder frequently has no importance in the sense of therapeutic possibility of the disease, its value can be seen in proper information of possibility of disease transmission as well as in prediction of affected person’s life perspective, associated with the decrease of visual acuity.